PENGARUH STRUKTUR KEPEMILIKAN NEGARA DAN KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA KEUANGAN BADAN USAHA MILIK NEGARA DI INDONESIA - Hardi Anando Pratama; Warsito Kawedar (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of the structure of state ownership, company size, financial leverage, reliability of financial statements, AIP, and level of competitiveness on SOE financial performance. The population in this study is all state-owned companies in Indonesia, while the sample in this study from the Laporan Hasil Pemeriksaan atas Laporan Keuangan Pemerintah Pusat (LHP LKPP) in 2017 selected by purposive sampling method. Data analysis techniques using (1) Descriptive Statistics Test (2) Classical Assumptions Test (3) Hypothesis Test. The findings in this study indicate that company size and financial leverage have a significant negative effect on financial performance. Meanwhile the level of competitiveness has a significant positive effect on financial performance. And the structure of state ownership, financial report reliability, and AIP have no significant effect on financial performance.